Induction of microvascular network growth in the mouse mesentery. (10th October 2018) - Suarez‐Martinez, Ariana D.; Peirce, Shayn M.; Isakson, Brant E.; Nice, Matthew; Wang, Jack; Lounsbury, Karen M.; Scallan, Joshua P.; Murfee, Walter L.
Abstract: Objective: Motivated by observations of mesenteries harvested from mice treated with tamoxifen dissolved in oil for inducible gene mutation studies, the objective of this study was to demonstrate that microvascular growth can be induced in the avascular mouse mesentery tissue. Methods: C57BL/6 mice were administered an IP injection for five consecutive days of: saline, sunflower oil, tamoxifen dissolved in sunflower oil, corn oil, or peanut oil. Results: Twenty‐one days post‐injection, zero tissues from saline group contained branching microvascular networks. In contrast, all tissues from the three oils and tamoxifen groups contained vascular networks with arterioles, venules, and capillaries. Smooth muscle cells and pericytes were present in their expected locations and wrapping morphologies. Significant increases in vascularized tissue area and vascular density were observed when compared to saline group, but sunflower oil and tamoxifen group were not significantly different. Vascularized tissues also contained LYVE‐1‐positive and Prox1‐positive lymphatic networks, indicating that lymphangiogenesis was stimulated. When comparing the different oils, vascularized tissue area and vascular density of sunflower oil were significantly higher than corn and peanut oils. Conclusions: These results provide novel evidence supporting that induction of microvascular network growth into the normally avascular mouse mesentery is possible.